XRN2 suppresses aberrant entry of tRNA trailers into argonaute in humans and Arabidopsis. - Briana Wilson; Zhangli Su; Pankaj Kumar; Anindya Dutta (PLoS Genetics)
MicroRNAs (miRNAs) are a well-characterized class of small RNAs (sRNAs) that regulate gene expression post-transcriptionally. miRNAs function within a complex milieu of other sRNAs of similar size and abundance, with the best characterized being tRNA fragments or tRFs. The mechanism by which the RNA-induced silencing complex (RISC) selects for specific sRNAs over others is not entirely understood in human cells. Several highly expressed tRNA trailers (tRF-1s) are strikingly similar to microRNAs in length but are generally excluded from the microRNA effector pathway. This exclusion provides a paradigm for identifying mechanisms of RISC selectivity. Here, we show that 5' to 3' exoribonuclease XRN2 contributes to human RISC selectivity. Although highly abundant, tRF-1s are highly unstable and degraded by XRN2 which blocks tRF-1 accumulation in RISC. We also find that XRN mediated degradation of tRF-1s and subsequent exclusion from RISC is conserved in plants. Our findings reveal a conserved mechanism that prevents aberrant entry of a class of highly produced sRNAs into Ago2.